SPATIAL DISTRIBUTION AND STRUCTURAL VARIATION OF Copaifera arenicola IN A CAATINGA FRAGMENT - Gama, Dráuzio Correia; Ferreira, Robério Anastácio; Jesus, Janisson Batista de; Nascimento Júnior, José Monteiro do (Floresta, 2020)
The study of spatial distribution of tree populations has proven to be important for revealing how individuals are horizontally organized in the environment, facilitating the structural understanding and forms of colonization and dispersion of propagules. The present work aimed at studying the pattern of spatial distribution of tree species Copaiferaarenicola [(Ducke) J. Costa e L.P.Queiroz] and its structural relation with the altimetric profile in a Caatinga fragment in Ribeira do Pombal municipality, Bahia. Census of all individuals in the area with circumference at breast height (CBH) ≥ 6 cm was performed. The spatial distribution analysis was conducted for the whole population using Ripley K univariate function, with maximum search radius (h) of 128 m. 409 individuals were found, corresponding to absolute density of 89.49 ind. ha-1 and 0.681 m². ha-1 of basal area. The group of C. arenicola individuals corresponds to a stable population in expansion phase, presenting higher number of young and medium individuals. The pattern of spatial distribution of individuals in the area under study was the uniform arrangement. None of the altimetric classes of the area had a different influence on the structure and distribution of arboreal individuals.